IDENTIFIKASI PENDEKATAN DALAM PENANGANAN KONFLIK DAN PENGARUHNYA TERHADAP KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAERAH KABUPATEN SANGGAU PROVINSI KALIMANTAN BARAT - Edy Sutrisno; Novi Desanti (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2018)
ABSTRACT The topic of this research is purposed to identify the conflict handling and to analyze the influence that has done by BKD Kab. Sanggau. The method used in this research is quantitative by involving 34 samples and also the multiple linear regression analysis is used here as the analysis technic. The variable measurement is done by using Likert scale and applied variously based on the question. The result in this kind of technic analysis showed that there is a parsially significant effect of the conflict handling that fulfilled and interacted against the performance. On the other side, conflict handling by dominating, compromising, and avoiding partially is not significantly affect the performance. If seen simultaneously, the conflict handling also isn’t affect it. However, as can be seen in signification score of the conflict handling is by fulfilling and giving the massive influence to the performance. Keywords: conflict, conflict handling, performance